Multiwavelength study of Cygnus A IV. Proper motion and location of the nucleus - Steenbrugge, K; Blundell, K; Pyrzas, S (EDP Sciences, 2014)
Context. Cygnus A, as the nearest powerful FR II radio galaxy, plays an important role in understanding jets and their impact on the surrounding intracluster medium. Aims. To explain why the nucleus is observed superposed onto the eastern lobe rather than in between the two lobes, and why the jet and counterjet are non-colinear. Methods. We made a comparative study of the radio images at different frequencies of Cygnus A, in combination with the published results on the radial velocities in the Cygnus A cluster. Results. From the morphology of the inner lobes we conclude that the lobes are not interacting with one another, but are well separated, even at low radio frequencies. We explain the location of the nucleus as the result of the proper motion of the galaxy through the cluster. The required proper motion is of the same order of magnitude as the radial velocity offset of Cygnus A with the sub-cluster it belongs to. The proper motion of the galaxy through the cluster likely also explains the non-co-linearity of the jet and counterjet.